Money : how the destruction of the dollar threatens the global economy--and what we can do about it - Forbes, Steve, 1947-; Ames, Elizabeth (McGraw Hill-Ascent Audio, 2014)
***Updated content to coincide with the public television documentary, In Money We Trust*** Why a return to sound money is our only hope for a true recovery and a healthy global economy Few topics are as misunderstood today as the subject of money. Since the U.S. abandoned a gold-linked dollar more than four decades ago, the world's governments have slid into a dangerous ignorance of the fundamental monetary principles that guided the world's most successful economies for centuries. Today's wrong-headed monetary policies are now setting the stage for a new global economic and social catastrophe that could rival the recent financial crisis and even the horrors of the 1930s. Coauthored by Steve Forbes, one of the world's leading experts on finance, Money shows you why that doesn't need to happen--and how to prevent it. After reading this entertaining and hugely well-informed book, you will know more about money than most people in the highest government positions today. Money explains why a return to sound money is absolutely essential if the U.S. and other nations are ever to overcome today's problems. Stable money, Steve Forbes and Elizabeth Ames argue, is the only way to a true recovery and a stable and prosperous economy. Today's system of fluctuating "fiat" money, in which governments manipulate the value of the dollar and other currencies, has been responsible for the biggest economic failures of recent decades, including the 2008 financial crisis, from whose effects we continue to suffer. The Obama/Bernanke/Yellen Federal Reserve and its unstable dollar policies are accelerating our course toward disaster, the authors show, in numerous convincing examples. In Money, Forbes and Ames answer these crucial questions: What is the difference between money and value?What is real wealth? How does sound money contribute to a well-functioning society? How have our money policy errors led to the current problems in global financial markets? What can we do now to reestablish the strength of the dollar and other currencies? The authors argue that the most effective way to return to a sound money policy and a healthy economy is to put the dollar back on a gold standard, and they outline the several different forms a gold standard could take. They also share invaluable suggestions for how to preserve our wealth and where to invest our money. Money is essential reading for anyone interested in this crucially important subject.